2021
DOI: 10.1038/s41467-021-25060-1
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular chaperone Clusterin enhances Tau aggregate seeding in a cellular model

Abstract: Spreading of aggregate pathology across brain regions acts as a driver of disease progression in Tau-related neurodegeneration, including Alzheimer’s disease (AD) and frontotemporal dementia. Aggregate seeds released from affected cells are internalized by naïve cells and induce the prion-like templating of soluble Tau into neurotoxic aggregates. Here we show in a cellular model system and in neurons that Clusterin, an abundant extracellular chaperone, strongly enhances Tau aggregate seeding. Upon interaction … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 97 publications
1
51
0
Order By: Relevance
“…To test whether AP-3μ1 is also sequestered by natural amyloids, we analyzed its colocalization with aggregates formed by the Tau repeat domain (TauRD, residues 244-372 with the point mutations P301L/ V337M, fused to EYFP), which mediates the assembly of tau fibrils (Crowther et al, 1992). Neurons transduced with TauRD-EYFP were treated with recombinant TauRD seeds to induce aggregation (Fig 7F) (Yuste-Checa et al, 2021). We observed significantly higher colocalization between TauRD-EYFP and endogenous AP-3μ1 in neurons treated with seeds compared with non-seeded control cultures (Fig 7F and G).…”
Section: Ap-3μ1 Is Sequestered By β Protein Aggregates Compromising the Integrity Of The Ap-3 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…To test whether AP-3μ1 is also sequestered by natural amyloids, we analyzed its colocalization with aggregates formed by the Tau repeat domain (TauRD, residues 244-372 with the point mutations P301L/ V337M, fused to EYFP), which mediates the assembly of tau fibrils (Crowther et al, 1992). Neurons transduced with TauRD-EYFP were treated with recombinant TauRD seeds to induce aggregation (Fig 7F) (Yuste-Checa et al, 2021). We observed significantly higher colocalization between TauRD-EYFP and endogenous AP-3μ1 in neurons treated with seeds compared with non-seeded control cultures (Fig 7F and G).…”
Section: Ap-3μ1 Is Sequestered By β Protein Aggregates Compromising the Integrity Of The Ap-3 Complexmentioning
confidence: 99%
“…Typically, 1 μl/cm 2 of virus was added, but this amount was sometimes adjusted to match protein expression levels among different constructs. TauRD (residues 244-371, C291A/P301L/C322A/ V337M) seeds were kind gift of Patricia Yuste-Checa and were prepared as described (Yuste-Checa et al, 2021). Seeding was performed on DIV 10+3 by adding 70 ng of TauRD seeds mixed with fresh medium (1-10th of the medium in the well) to the neuronal cultures in 24-well plates.…”
Section: Primary Neuron Culturementioning
confidence: 99%
“…We speculated that the disaggregation activity of VCP could modulate the levels of aggregate species that are able to induce the aggregation of soluble Tau in recipient cells. To address this possibility, we measured the presence of seeding-competent TauRD species by FRET in cells expressing TauRD-mTurquoise2 and TauRD-Y (TauRD-TY cells) 62 (Fig. 6a).…”
Section: Resultsmentioning
confidence: 99%
“…Cell lines and cell culture Cells expressing constitutive and tet-regulated TauRD-Y (TauRD-Y and Tet-TauRD-Y cell lines, respectively), FRET biosensor TauRD-TY, and FLTau-Y cells were previously described 37,62 . Tet-FLTau and Tet-TauRD cell lines were generated by transducing HEK293T cells with 200 µL concentrated lentivirus in presence of 0.8 µg/mL Polybrene (Sigma).…”
Section: Plasmidsmentioning
confidence: 99%
“…For example, the first experiments of DeMattos et al [137] have suggested that CLU promotes Aβ toxicity, but in their subsequent findings [131] the collaboration of CLU with ApoE in limiting the generation of toxic Aβ aggregates (and resulting neurodegeneration) has been observed. Nevertheless, although CLU seems to function mainly towards neuroprotection, there are studies that suggest its neurotoxic properties, as observed in the recent experiments by Yuste-Checa et al [138].…”
Section: Clusterin In the Cns-upregulation And Possible Neuroprotecti...mentioning
confidence: 95%